Associations between vitamins intake and risk of cancer in United States adults: 2003 to 2016 national health and nutrition examination survey - Wen, Youfei; Yang, Xiuzhen; Huang, Yan (Frontiers in Nutrition, 2025)
IntroductionNational Health and Nutrition Examination Survey (NHANES) is a cross-sectional survey that gathered information about people’s health and nutrition. The aim of this study is to investigate potential associations between vitamin intake and cancer risk using this database.MethodsThe NHANES data set encompassed a wide range of variables, including vitamins, cancer, and others. Logistic regression models, restricted cubic splines (RCS) and subgroup analysis were used to test the potential link between vitamin consumption and cancer risk.ResultsIn total, 29, 138 individuals were included in this study, while 2,924 of them had a diagnosis of cancer. The odds of developing cancer were reduced for persons consuming the highest quartile of dietary niacin compared to those consuming the lowest quartile [odds ratio (OR) = 0.78, 95% confidence range = 0.65, 0.95, p = 0.015]. However, after adjusting for all confounding factors, as the intake of vitamin A gradually increased, the risk of tumor occurrence correspondingly increased (OR = 1.38, 95% CI 1.13, 1.69, p = 0.002). Subgroup analysis and RCS models showed similar results. Only when the intake of folic acid is 267–367 mcg, folic acid is positively correlated with the risk of tumors. Vitamins E, B1, B2, B6, B12, C, K, alpha-carotene and beta-carotene were not associated with the risk of tumor development.ConclusionVitamin A intake is positively correlated with the occurrence of tumors, while niacin intake is negatively correlated with the incidence of tumors. Further longitudinal studies are needed to verify these findings.